2001
DOI: 10.1093/humrep/16.8.1676
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, randomized comparison of two starting doses of recombinant FSH in combination with cetrorelix in women undergoing ovarian stimulation for IVF/ICSI

Abstract: When using a starting dose of 225 IU rhFSH combined with the multiple dose of 0.25 mg cetrorelix from stimulation day 6, significantly more oocytes were obtained than with a starting dose of 150 IU rhFSH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(25 citation statements)
references
References 12 publications
3
19
0
3
Order By: Relevance
“…There was prominent difference among aspirated oocytes between groups in favor of the agonist treatment and similar data were reported for the agonist group in long protocol by Ludwig et al (18). It was suggested that the short induction period of the antagonist group causes these low numbers of oocytes and Wikland et al (19) reported that increasing doses of gonadotropins in antagonist cycles may provide significantly higher numbers of oocytes. However, in our study, although both groups had similar stimulation periods and gonadotropin doses, the antagonist group had significantly lower numbers of oocyte.…”
Section: Discussionsupporting
confidence: 65%
“…There was prominent difference among aspirated oocytes between groups in favor of the agonist treatment and similar data were reported for the agonist group in long protocol by Ludwig et al (18). It was suggested that the short induction period of the antagonist group causes these low numbers of oocytes and Wikland et al (19) reported that increasing doses of gonadotropins in antagonist cycles may provide significantly higher numbers of oocytes. However, in our study, although both groups had similar stimulation periods and gonadotropin doses, the antagonist group had significantly lower numbers of oocyte.…”
Section: Discussionsupporting
confidence: 65%
“…Two studies were identified that used GnRH-antagonists for pituitary suppression. One compared a starting dose of 150 IU with 200 IU [17], whereas the other compared 150 IU with 225 IU [18]. A summary of the relevant data is provided in Table 2 and Fig.…”
Section: Expected Normal Respondersmentioning
confidence: 99%
“…In another study Ben-Rafael et al, [25] found fewer atretic oocytes (p< 0.05) and a higher pregnancy rate (22.8 versus 10.5%, not significant) in patients receiving two ampoules of HMG compared to those receiving three ampoules. Some studies comparing the use of two different doses of rFSH in antagonist cycles (150 vs 200 rFSH or 150 vs. 225 rFSH) found that the number of oocytes retrieved was higher using a higher dose of rFSH (p<0.05), but the proportion of high quality embryos and implantation rate were higher with the lower dose of rFSH (not significant) [26,27]. Out et al [22,28] comparing starting doses of 100 IU vs 200 IU rFSH or 150 IU vs. 250 IU rFSH in long agonist protocols also found higher pregnancy rates and implantation rates with the lowdose regimens, although differences were not statistically significant.…”
Section: Discussionmentioning
confidence: 99%